THE BALTIC SEA REGION AND EU MARITIME SAFETY - Teresa Usewicz (Colloquium, 2022)
The article concerns the Baltic Sea region in the context of the maritime security of the European Union. The research problems in this article are therefore limited to the questions: how is the Baltic Sea region defined in scientific literature? How is the concept of maritime safety and security defined in political-strategic documents and literature? And also, what is the role of the Baltic Sea region in building the European Union's maritime safety? The article attaches particular importance to issues related to the multidimensional and ambiguous nature of concepts of maritime safety and security, and the maritime safety of a state, in terms of the functioning of the EU. The Baltic Sea and its specific characteristics affecting maritime safety in the region have also been analysed. The conclusions of the conducted research may serve as guidance in shaping maritime safety in the Baltic Sea region.